ANALISIS LAGU RAYUAN PULAU KELAPA ARANSEMEN SINGGIH SANJAYA UNTUK PADUAN SUARA - Herlina Herlina; Jagar Lumbantoruan; Marzam Marzam (FBS Universitas Negeri Padang, 2018)
Abstract The purpose of this study was to analyze and describe the arrangement of the Rayuan Pulau Kelapa song by Singgih Sanjaya based on the principles of melodic and harmonic principles. This type of research was qualitative with a content analysis approach. The theory used was to explain how the sound arrangement of the Rayuan Pulau Kelapa song by Singgih Sanjaya based on harmonic principles and melodic principles. The supporting data of this research were derived from literature studies, interviews and laboratory work. The result of the research is that the song has two forms, AA1B in arranging using harmonics-tone (major and minor chords principles), and non-harmonic-tones. In a pattern, working on a typical song that appears in the Singgih Sanjaya arrangement is the movement of tones between the four voices that do not move in parallel. Motuses between soprano and alto tend to be parallel (motus rectus), motus between soprano and deviant tenor (motus obliqus) and motus between soprano and bass also tend to deviate (motus obliqus). In addition, Singgih Sanjaya adopts conventional counterpoint theory of Western Music, where the sound on the cantus firmus is not always in Soprano (moving). So it can be concluded that in arranging the song, Singgih Sanjaya uses polyphony techniques and refer to the harmonic principles and melodic principles. Keywords: Form analysis, chord progression and cadence, motus, counterpoint, melodic and harmonic principles.